Objectivity in History: An Analysis (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The controversy as to whether or not historical truth is objective is as old as the profession itself. However the issue became a hotly debated point of contention only after Ranke openly and confidently declared that truth in history was not only objective but achievable. Though initially Ranke's argument found great support from historians all over Europe, and the United States as well, however by the beginning of the 20th century scepticism began to be raised among philosophers and philosophically minded historians on the accuracy of historical accounts written by historians. One of the reasons for this scepticism was the belief that historical explanation was not based on any empirical or scientific methods but rather expressed by the historian based on his personal assumption of what could possibly have happened. As such, it was argued that historical truth could at best be true only relative to the values and needs of the time of the historian who writes it. Due to their emphasis on relativism these critics later came to be referred as Relativists. The debate between the Relativists and those who staunchly believe that history is objective and achievable continues to this day. This article makes a modest attempt to analyse the objections put forth by the Relativists against objectivity to argue that history, indeed, is objective and also achievable.